First aid training in secondary schools: A comparative study and implementation considerations. (December 2020) - Reveruzzi, Bianca; Buckley, Lisa; Sheehan, Mary
Highlights: For adolescents, first aid training is associated with greater knowledge to 12-months. Greater knowledge found with SPIY compared with first aid as-usual and no training. Training was associated with greater knowledge in select areas. Abstract: Introduction: School-based first aid training has benefits for adolescents with an opportunity to increase health and safety knowledge relating to injury and cardiac arrest. Method: Using a quasi-experimental design we evaluated differences among students ( M age  = 13.46 years, 55% female) taught first aid through the Skills for Preventing Injury in Youth (SPIY) program ( n  = 1942), treatment-as-usual school-based first aid training ( n  = 675), and students who did not receive first aid training ( n  = 489). Results: Results showed significant differences in self-reported knowledge scores at twelve-month follow-up (controlling for baseline knowledge). Students in the SPIY group and the treatment-as-usual first aid group had higher total scores than the control group. Teachers and students reported positive perceptions to first aid study, in particular the interactive delivery and scenarios for contextualizing information. Practical Applications: The study provides support for the retention of first aid knowledge up to 12-months and thus the inclusion and feasibility of first aid training in secondary school curriculum.